2009
DOI: 10.1242/dev.032714
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of three long-range enhancers directs regionalShhexpression in the epithelial linings

Abstract: The sonic hedgehog (Shh) pathway plays indispensable roles in the morphogenesis of mouse epithelial linings of the oral cavity and respiratory and digestive tubes. However, no enhancers that regulate regional Shh expression within the epithelial linings have been identified so far. In this study, comparison of genomic sequences across mammalian species and teleost fishes revealed three novel conserved non-coding sequences (CNCSs) that cluster in a region 600 to 900 kb upstream of the transcriptional start site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 65 publications
9
125
0
Order By: Relevance
“…Although Shh is expressed in both appendages, its expression in the ZPA and that in the hindgut are regulated by different enhancers. Hindgut Shh expression relies on DNA elements that are not conserved between mammals and the teleost fish medaka (Sagai et al, 2009), whereas those controlling ZPA Shh expression are highly conserved (Lettice et al, 2008;Sagai et al, 2005). These findings suggest a differential acquisition of Shh expression in the evolution of the two appendages.…”
Section: Shh Due and Genital Evolutionmentioning
confidence: 92%
“…Although Shh is expressed in both appendages, its expression in the ZPA and that in the hindgut are regulated by different enhancers. Hindgut Shh expression relies on DNA elements that are not conserved between mammals and the teleost fish medaka (Sagai et al, 2009), whereas those controlling ZPA Shh expression are highly conserved (Lettice et al, 2008;Sagai et al, 2005). These findings suggest a differential acquisition of Shh expression in the evolution of the two appendages.…”
Section: Shh Due and Genital Evolutionmentioning
confidence: 92%
“…The upregulation of hedgehog pathway expression in the pDKO mice suggested that Shh might be repressed by GATA4 and/or GATA6. An 806-bp MACS1 enhancer located ∟740 kb upstream from the Shh transcriptional start site has been shown to be sufficient for driving Shh expression specifically in the foregut endoderm (Anderson et al, 2014;Sagai et al, 2009). Using position weight matrix analysis we identified four putative GATA consensus elements within the MACS1 enhancer (Fig.…”
Section: Cell Fate Switching Occurs In the Pdko Pancreatic Endodermmentioning
confidence: 99%
“…The spatial and temporal Shh expression pattern results from the combined action of multiple enhancer elements present in its extensive regulatory domain, controlling Shh transcription in different tissues [12][13][14][15][16]. However, only recently specific transcription factors have been discovered to directly control Shh enhancer activity.…”
mentioning
confidence: 99%